2014 IEEE International Symposium on Mixed and Augmented Reality (ISMAR) 2014
DOI: 10.1109/ismar.2014.6948413
|View full text |Cite
|
Sign up to set email alerts
|

A study of depth perception in hand-held augmented reality using autostereoscopic displays

Abstract: Displaying three-dimensional content on a flat display is bound to reduce the impression of depth, particularly for mobile video see-trough augmented reality. Several applications in this domain can benefit from accurate depth perception, especially if there are contradictory depth cues, like occlusion in a x-ray visualization. The use of stereoscopy for this effect is already prevalent in headmounted displays, but there is little research on the applicability for hand-held augmented reality. We have implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
(20 reference statements)
0
22
0
Order By: Relevance
“…Distortion of depth perception is a common problem in AR [3,7]. This issue relates to the perception of size and distance of the VOs regarding the ROs and real space.…”
Section: Related Work 21 Perceptual Issues In Armentioning
confidence: 99%
“…Distortion of depth perception is a common problem in AR [3,7]. This issue relates to the perception of size and distance of the VOs regarding the ROs and real space.…”
Section: Related Work 21 Perceptual Issues In Armentioning
confidence: 99%
“…Hence, the user's level of engagement may be impeded by such unnatural interactions. Finally, handheld AR has been demonstrated to not significantly impact cybersickness (Berning et al, 2014), though it may cause arm fatigue due to holding the smartphone or tablet (LaViola et al, 2017).…”
Section: Handheld Armentioning
confidence: 99%
“…Three participants mentioned that they used the shadows cast by the excavator crane, instead of relying on the AR guides. In related studies, Berning et al [55] determined that monoscopic cues dominate over stereoscopic depth cues in depth perception, and Diaz et al [57] specifically showed the importance of shadow cues for position estimation. This aspect may also explain why the influence of changing viewing position, which changes the visibility of monocular positioning cues, was much greater than the influence of using different AR designs.…”
Section: Discussionmentioning
confidence: 99%
“…In a non-headset environment with volumetric and 2-Dimensional (2D) AR see-through displays, Lisle et al [2] found that AR shown on volumetric 3D displays outperformed AR shown on 2D panels for estimating depths greater than 5 m, which also implies a potential benefit of 3D AR in headset-based environments for specific task performance. In mixed depth cue environments, Berning et al [55] showed that monoscopic cues dominate over stereoscopic cues, however stereoscopy assists in challenging tasks. These findings extended the earlier work of Nagata [56], which showed the impact of distance on real world depth cue dominance.…”
Section: Depth Perception In Virtual Augmented Environmentsmentioning
confidence: 99%